Transcriptomic characterisation of the optimised rat model of Walker 256 breast cancer cell‐induced bone pain. (15th September 2019) - Shenoy, Priyank A.; Kuo, Andy; Leparc, German; Hildebrandt, Tobias; Rust, Werner; Nicholson, Janet R.; Corradini, Laura; Vetter, Irina; Smith, Maree T.
Abstract: In patients with breast cancer, metastases of cancer cells to the axial skeleton may cause excruciating pain, particularly in the advanced stages. The current drug treatments available to alleviate this debilitating pain condition often lack efficacy and/or produce undesirable side effects. Preclinical animal models of cancer‐induced bone pain are key to studying the mechanisms that cause this pain and for the success of drug discovery programs. In a previous study conducted in our laboratory, we validated and characterised the rat model of Walker 256 cell‐induced bone pain, which displayed several key resemblances to the human pain condition. However, gene level changes that occur in the pathophysiology of cancer‐induced bone pain in this preclinical model are unknown. Hence, in this study, we performed the transcriptomic characterisation of the Walker 256 cell line cultured in vitro to predict the molecular genetic profile of this cell line. We also performed transcriptomic characterisation of the Walker 256 cell‐induced bone pain model in rats using the lumbar spinal cord and lumbar dorsal root ganglia tissues. Here we show that the Walker 256 cell line resembles the basal‐B molecular subtype of human breast cancer cell lines. We also identify several genes that may underpin the progression of pain hypersensitivities in this condition, however, this needs further confirmatory studies. These transcriptomic insights have the potential to direct future studies aimed at identifying various mechanisms underpinning pain hypersensitivities in this model that may also assist in discovery of novel pain therapeutics for breast cancer‐induced bone pain.